Can it happen here? : authoritarianism in America - Sunstein, Cass R. (Dey St., an imprint of William Morrow, 2018)
"With the election of Donald J. Trump, many people on both the left and right feared that America's 240-year-old grand experiment in democracy was coming to an end, and that Sinclair Lewis' satirical novel, It can't happen here, written during the dark days of the 1930s, could finally be coming true. Is the democratic freedom that the United States symbolizes really secure? Can authoritarianism happen in America? [The editor] queried a number of the nation's leading thinkers. In this ... collection of essays, these ... thinkers and theorists explore the lessons of history, how democracies crumble, how propaganda works, and the role of the media, courts, elections, and 'fake news' in the modern political landscape--and what the future of the United States may hold."--